Dimension of Dialectic Politics - Thapa, Mahendra Bhushan (Journal of Political Science, 2004)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The world is guided by power politics. The power politics is the core process for regulating human behaviour activised in the society. The society is regulated and maintained with the provision of law and order sanctioned by power politics. Everybody has strong willingness for gaining power for the fulfilment of the self-interest and also for the betterment of the society. But from the view point of human nature, self-interest is more stronger than the interest in the society. The objective of this article is to analyze power politics for the fulfilment of human interest based on the struggle for power. Journal of Political Science Vol.7(1) 2004 20-28